Organizational climate and work commitment as predictor of 10-year registered sickness absence. (13th November 2019) - Knapstad, M; Lissner, L; Bjorkelund, C; Holmgren, K
Abstract: Background: Early identification of persons at risk for sickness absence offers an opportunity to put in place preventive measures in the future. The Work Stress Questionnaire (WSQ) is specifically designed to identify people at risk for sickness absence due to work-related stress. In this study we examine prospective associations between work-related stress as measured by the WSQ and registered sickness absence up till 10 years later among employed and self-employed women in the general population in Gothenburg. Methods: This is a survey-linkage study based on the 2004-05 wave of the Swedish "Population Study of Women in Gothenburg (PSWG)" and 10-year follow-up in the MiDAS sickness absence register. Participants registered as employed or self-employed were included (n = 396). Outcomes were number of sickness absence episodes during follow-up and sickness absence during each two-year time band of follow-up. Results: High perceived stress due to poor organizational climate, compared to low stress, gave an adjusted Incidence Risk Rate (IRR) of 1.99 [95% CI 1.19-3.34] for sickness absence episodes. Combining high perceived stress due to poor organizational climate with high perceived stress due to work commitment gave an IRR of 2.32 [95% CI 1.26-4.26]. Examining separate time periods, similar associations were found during years 5-6 and 7-8. Perceived low influence at work also gave increased odds for sickness absence, at both in the shorter term (1st-2nd year) and longer term (7th-8th year). Conclusions: The findings align with previous studies that WSQ may successfully identify women with elevated risk for future sickness absence, and adds that this is even true in a general population context and using a very long follow-up period. Nevertheless, the findings should preferably be confirmed using a larger sample to improve precision of the observed associations. Key messages: The present study contribute with knowledge about screening instruments that may identify women in the general working population with elevated risk for sickness absence. The findings suggest that high perceived stress due to organizational climate, alone and in combination with high work commitment, as well as low influence at work, increase risk of sickness absence.